The Development of Wind Power under the Low-Carbon Constraints of Thermal Power in the Beijing-Tianjin-Hebei Region - Guo, Xiaopeng; Yang, Xiaoyu (IEEE access, 2020)
Thermal power has consumed a lot of coal, which causes serious air pollution in the Beijing-Tianjin-Hebei region. Previous studies on low-carbon development often separated the three regions, ignoring the coordinated development relationships in the regions. Under the low-carbon development constrictions of thermal power, this paper studied the development of wind power. Firstly, from the integration development of the Beijing-Tianjin-Hebei region, the changes in industrial structure and the total electricity consumption were predicted. Secondly, a comprehensive analysis of the low-carbon development policy for these regions, in accordance with the analytical results, controls the development of thermal power. Finally, a system dynamics model is used to analyse the wind power development from 2018 to 2025 under the influence of development on purchased electricity, the development of thermal and wind power policy. The study found that under the existing policies the Beijing-Tianjin-Hebei region can achieve the goal of installed wind power capacity in the "13th Five-Year Plan for Electrical Power Development". And from 2020 to 2025, the installed capacity of wind power significantly increases. Based on sensitivity analysis for wind power development, installed wind power capacity is the most sensitive to the wind power feed-in tariff, followed by thermal power generation capacity and then purchased electricity. To prevent wind power growing too fast, this paper suggests reducing the feed-in tariff of wind power during the "14th Five-Year Plan".